Stability of Crushed Tedizolid Phosphate Tablets for Nasogastric Tube Administration - Kennedy, Gerard (Drugs R D, 2015)
Tedizolid phosphate is approved for the treatment of acute bacterial skin and skin structure infections. To determine whether the expected dose of tedizolid phosphate can be delivered via nasogastric tube in patients who have difficulty swallowing and in whom venous access is not suitable, this in vitro study evaluated the recovery of tedizolid phosphate 200-mg tablets after crushing, dispersion in water, and passage through a nasogastric tube. To analyze the chemical stability of the crushed tablet dispersed in water, the aqueous preparation was assayed initially after dispersion and again after 4 h at room temperature. Recovery of tedizolid phosphate after the crushed tablets were dispersed in water and passed through nasogastric tubes ranged from 92.5 to 97.1 %, which is within the specified acceptance criteria of 90 to 110 %. There was no significant change in recovery values after 4 h of storage at room temperature (93.9 % initially and 94.7 % after 4 h). The stability and recovery findings support the feasibility of administering an aqueous dispersion of crushed tedizolid phosphate tablets through a nasogastric tube in patients who have difficulty swallowing and in whom intravenous administration is not possible.